2020
DOI: 10.1002/csr.1930
|View full text |Cite
|
Sign up to set email alerts
|

How do the size and independence of the board of trustees affect the financial and sustainable performance of socially responsible mutual funds?

Abstract: In this article, I study for first time how the board of trustees’ size and independence influence the financial performance and sustainability scores of socially responsible (SR) mutual funds. The sample analyzed consists of 99 SR US domestic equity mutual funds existing in the period 2012–2018. The results obtained indicate that funds monitored by boards with a lower number of trustees and an independent chair show lower net expense ratios and better sustainability scores. In addition, smaller boards and a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
(108 reference statements)
2
6
0
Order By: Relevance
“…Adams et al. (2018) and Muñoz (2020) also found a negative and significant relationship between the age of the fund and its financial performance. The positive effect of the fund's size could be explained by the existence of economies of scale, as documented by Latzko (1999).…”
Section: Empirical Findingsmentioning
confidence: 89%
“…Adams et al. (2018) and Muñoz (2020) also found a negative and significant relationship between the age of the fund and its financial performance. The positive effect of the fund's size could be explained by the existence of economies of scale, as documented by Latzko (1999).…”
Section: Empirical Findingsmentioning
confidence: 89%
“…A recent study by Zubeltzu-Jaka et al (2020) reported that larger boards enable companies to achieve social objectives as stakeholder sensitivities are better represented. On the other hand, Muñoz (2020) reported that board size has negative relationships with corporate social performance. Other researchers, like Cucari et al (2018), found no significant relationship between board size and corporate social activities.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Much of the SR mutual fund literature focusses on comparisons between the financial performance of these funds and conventional funds (Bauer et al, 2005;Signori, 2009;Leite and Cortez, 2014;or Ur Rehman et al, 2016;etc). Other authors have analysed the effect of different approaches to integrating ESG issues into the investment process on the financial performance of SRMFs (Hernaus, 2019;or Muñoz, 2020) or the financial performance of specific subsets of SRMFs (see amongst others Ferruz et al (2012), who analyse religious funds or Muñoz et al (2014), who study environmental funds). Some studies have analysed the financial performance of SRMFs controlling for investment style exposure (Das and Rao, 2013;Leite and Cortez, 2014;or Muñoz et al, 2015;etc); we found no articles examining deviations from these styles and their consequences.…”
Section: Socially Responsible Mutual Funds Literature and Research Hypothesesmentioning
confidence: 99%